MATHEMATICAL MODEL OF THE GEOMECHANICAL STATE OF THE UPPER PART OF THE EARTH'S CRUST BASED ON SALOME-MECA - Sydyk, N.S.; Bibossinov, A.Zh.; Nurakynov, S.M. (Academic Scientific Journal of Computer Science, 2020)
This article provides a brief description of the Saloma-meca software platform. An approach to the analysis of the geodynamic state of the upper crust of urban areas based on Saloma-meca is described. A generalized block diagram of the work of software and mathematics is built. Geometric models of the earth's crust have been developed for the city of Almaty. Test calculations of the distribution of SSS for the untouched mountain range were carried out according to the averaged data of soil densities based on Saloma-meca for the initial approximation in calculating the stress-strain state of the earth's crust in Almaty.